Pengembangan Sistem Informasi Penjaminan Mutu Online untuk Perguruan Tinggi Muhammadiyah/'Aisyiyah menggunakan Framework Laravel - Pahlevi, Ryan Fitrian (JATISI, 2024)
This study explores the application of the Laravel Framework in developing an Online Quality Assurance Information System at Muhammadiyah/'Aisyiyah Universities (PTMA). According to the Indonesian Law No. 12 of 2012, Higher Education encompasses educational programs beyond secondary education and has three main functions: education, research, and community service. PTMA adds a special function, Al-Islam and Kemuhammadiyahan, making its functions fourfold (caturdharma). The Quality Assurance System (SPM) at PTMA is governed by the Internal Quality Assurance System (SPMI) and External Quality Assurance System (SPME). Laravel, with its Model-View-Controller (MVC) architecture, offers an efficient solution for developing a system that meets PTMA's specific needs. This study aims to assess the advantages of Laravel in enhancing the quality and effectiveness of quality management at PTMA, with the expectation of providing valuable insights for improving higher education quality and achieving the established quality standards.